Studi Interpretatif Tentang Pola Pengelolaan Keuangan Badan Layanan Umum (PPK-BLU) Pada Balai Besar Kesehatan Paru Masyarakat Surakarta - Litaswari, Inesti, Dra. RinaTrisnawati, Ak, Msi.Ph.D (2016)
This study was conducted to Describe and explain the concept of Financial Management at the Center for Lung Health Community Surakarta before becoming Public Service Agency. Describe and analyze the implementation of the Financial Management of Public Service Agency (PPK-BLU) at the Great Hall of the People Lung Health Surakarta. Describe and analyze the financial performance and financial statements of the Center for Public Health Lung Surakarta after implementing Financial Management Public Service Agency (PPK-BLU). Identify and explain the constraints faced by the Center for Public Health Lung Surakarta in financial performance and statements when implementing Financial Management Public Service Agency (PPK-BLU). This type of research is qualitative interpretative approach . The subjects were parties know BLUDs implementation and PPK-BLU particularly financial performance and financial reports as well as included in the criteria required informant. The subject of research is, Kasubbag BBK PM Surakarta Finance and Head of Accounting and Verification BBKPM Surakarta. Data analysis technique used is the interpretative analysis method. The results showed Before BBKPM Surakarta be BLU financial management using strategic plan for the medium-term planning. Meanwhile, budgeting document using the Work Plan Budget (RKA). Management of operating income earned directly deposited into the state treasury advance can only be used once deposited. Agencies not BLU also abstains debts and long-term investment. Implementation PPK-BLU in Surakarta BBKPM already well underway, BBKPM Surakarta already implementing the administrative requirements such as Business Strategy Plan, Business Plan Budget and Financial Statements using the Financial Accounting Standards as well as the Government Accounting Stan dards. After becoming BLU, performance BBKPM Surakarta in particular financial performance has increased from year to year. This proves that BBKPM Surakar ta already implementing PPK-BLU well. BBKPM Surakarta still facing obstacles in implementing PPK-BLU particularly financial performance including timely submission of financial statements, should make financial reports more than one financial statement, limited human resources in financial reporting, the limitations of existing applications, create reports manually and not realization subsidies patient ratio, making BBKPM Surakarta not meet Government targets expected score. Keywords: financial management, PPK-BLU, a large hall Lung Health Community